Case Report: Two cases of rare head injuries from Nepal [version 2; peer review: 2 approved, 1 approved with reservations] - Joe M. Das; Rashmi Sapkota; Apar Pokharel; Ashish Babu Aryal; Manish Mishra (F1000Research, 2021)
Background: There are a number of ways in which one can sustain a head injury. Even if you are doing simple household activities or going out for a morning walk, you cannot be sure of what type of injury awaits you. The source of injury may be a pressure cooker whistle acting as a projectile or a hailstone falling from the sky. Such injuries are common in Nepal, considering the socio-demographic and geographic conditions. In this article, we present two such very rare cases of head injury. Case Reports: The first case is a middle-aged woman who sustained an accidental injury to the face associated with fracture of frontal sinus and frontal contusion, following the impact from a high momentum projectile in the form of the pressure regulator of a pressure cooker. She underwent craniotomy and removal of the foreign body. In the second case, an elderly man sustained minor injury to the head following the fall of hail. The abrasions and contusions produced by the hail were managed conservatively. Since he did not have any clinical evidence of head injury, other than multiple abrasions with contusions in the scalp, he did not undergo any imaging studies. He did not have any neurological deficits. The postoperative period was uneventful for the first patient and she was followed up for one month. The second patient was lost to follow-up. Conclusion: Successful management of two very rare cases of head injuries from Nepal are reported. Proper care and maintenance of the house-hold utensils that are constantly used may protect people from head injuries.  Though natural calamities cannot always be avoided, simple measures like using an umbrella while going outdoors may protect individuals from head injuries due to hailstones.